PROTEASE PRODUCTION BY PENICILLIUM SP. LCJ228 UNDER SOLID STATE FERMENTATION USING GROUNDNUT OILCAKE AS SUBSTRATE: Life Sciences-Biology - V. BENLUVANKAR; G. ROSELINE JEBAPRIYA; J. JOEL GNANADOSS (International Journal of Life Science and Pharma Research, 2022)
The production of alkaline protease by Penicillium sp. LCJ228 was studied under solid state fermentation. Oilcakes such as groundnut oilcake, mahua oilcake, sesame oilcake, cotton seed oilcake and coconut oilcake were used as substrates. The best substrate for maximum protease production was found to be groundnut oilcake and a high protease activity was observed on the 6th day of growth. The effect of medium components and culture conditions for maximizing protease production was investigated by one factor at a time method. Glucose (20 g/L) was found to be the best carbon source for maximum protease production. Yeast extract (15 g/L) was found to be the best nitrogen source and casein (5 g/L) was a suitable inducer. A pH value of 9.0, an inoculum size of 2 g/kg solid substrate and a moisture content of 80% were optimal for maximum protease production. After optimization of conditions, a 2.2 fold increase in the protease production was observed. The study proved that Penicillium sp. LCJ228 was able to produce a very high level of protease under SSF using inexpensive oilcakes.